Source Credibility and Consumers' Responses to Marketer Involvement in Facebook Brand Communities: What Causes Consumers to Engage?. Issue 2 (2nd July 2016) - McLaughlin, Caitlin
ABSTRACT: This study examined how the source credibility facets of trustworthiness and likeability of content creators within Facebook brand communities influenced how brand community members coped with persuasive messages within the community. To measure this, the type and number of marketer messages were manipulated within stimuli Facebook brand communities to influence source trustworthiness. In addition, brand loyalty was measured as a reflection of source likeability. Results suggested participants preferred messages asking them for their opinion but did not change their coping strategies based on the number of marketer posts, indicating that trustworthiness was only marginally influential on persuasion coping strategies. Brand loyalty, however, was extremely influential—a finding which indicates that likeability had a large effect on community member persuasion coping strategies.